Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1902/jop.2012.120078
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor‐α and Porphyromonas gingivalis Lipopolysaccharides Decrease Periostin in Human Periodontal Ligament Fibroblasts

Abstract: Background: Periostin is a matricellular protein essential for tissue integrity and maturation and is believed to have a key function as a modulator of periodontal ligament (PDL) homeostasis. The aim of this study is to evaluate whether periodontal disease‐associated pathogen‐related virulence factors (endotoxins/lipopolysaccharides [LPS]) and proinflammatory cytokines alter the expression of periostin in PDL cells.Methods: Human PDL cultures were exposed to inflammatory mediators (tumor necrosis factor‐α [TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 46 publications
3
37
0
Order By: Relevance
“…The micro-environmental factors present within the damaged tissue have been well characterized and several groups have documented elevated TNFα levels in non-healing skin wound fluid [29][30][31]. Moreover, the anti-fibrotic influence of TNFα through suppression of TGFβ signaling is well documented [32][33][34][35]. We have shown here that non-healing wounds contain significant neutrophil infiltration and TNFα immunoreactivity in the wound bed, which has also been reported previously in pressure sores [36].…”
Section: Discussionsupporting
confidence: 86%
“…The micro-environmental factors present within the damaged tissue have been well characterized and several groups have documented elevated TNFα levels in non-healing skin wound fluid [29][30][31]. Moreover, the anti-fibrotic influence of TNFα through suppression of TGFβ signaling is well documented [32][33][34][35]. We have shown here that non-healing wounds contain significant neutrophil infiltration and TNFα immunoreactivity in the wound bed, which has also been reported previously in pressure sores [36].…”
Section: Discussionsupporting
confidence: 86%
“…We first examined Periostin production and secretion by epithelial and mesenchymal cells. Using a human keratinocyte cell line (NOK-SI) [18] and a primary culture of human fibroblasts (hPDL) [30], we found that both cell types produced Periostin (Figure 2A). Full length Periostin is a 93 kDa protein, and additional human Periostin isoforms range from 83 kDa to 87 kDa (from UniProtKB/Swiss-Prot database - Q15063).…”
Section: Resultsmentioning
confidence: 99%
“…Gingival fibroblasts and periodontal ligament cells produce POSTN only when stimulated by interleukin (IL)‐13 and IL‐14 cytokines, while TNF‐α and Porphyromonas gingivalis lipopolysaccharides (LPS) did not induce POSTN production . Moreover, in a study on fibroblasts stimulated with TNF‐α and Porphyromonas gingivalis LPS, a decreased expression of POSTN was noted . A ligature‐induced periodontitis model in rats demonstrated the downregulation of POSTN in sites with chronic periodontal inflammation.…”
Section: Discussionmentioning
confidence: 99%